2008
DOI: 10.1016/j.virol.2008.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Topological properties of the triple gene block protein 2 of Bamboo mosaic virus

Abstract: The triple gene block protein 2 (TGBp2) of Bamboo mosaic virus (BaMV) has been proposed to be a transmembrane protein; however, its features remain unclear. Here, we used biochemical approaches to determine its topological properties. Our data reveal that TGBp2 is mainly associated with the endoplasmic reticulum membrane. The resistance of TGBp2 in proteoliposomes, prepared from both the BaMV-infected tissues and in vitro reconstitution system, to both chemical extraction and trypsin digestion confirmed that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 50 publications
0
28
0
1
Order By: Relevance
“…As mentioned earlier, research with GFP–TGB2 and GFP–TGB3 fusion proteins has demonstrated that both TGB2 and TGB3 proteins are integral membrane proteins in the ER or ER-associated vesicles located at actin filaments (Morozov and Solovyev, 2003; Hsu et al, 2008). In relation to the role of TGB2 and TGB3 proteins for potexvirus vRNA trafficking to PD, two models have been proposed (Verchot-Lubicz et al, 2010; Chou et al, 2013).…”
Section: Intracellular Trafficking Of Potexvirus Vrna From the Cytoplmentioning
confidence: 92%
See 1 more Smart Citation
“…As mentioned earlier, research with GFP–TGB2 and GFP–TGB3 fusion proteins has demonstrated that both TGB2 and TGB3 proteins are integral membrane proteins in the ER or ER-associated vesicles located at actin filaments (Morozov and Solovyev, 2003; Hsu et al, 2008). In relation to the role of TGB2 and TGB3 proteins for potexvirus vRNA trafficking to PD, two models have been proposed (Verchot-Lubicz et al, 2010; Chou et al, 2013).…”
Section: Intracellular Trafficking Of Potexvirus Vrna From the Cytoplmentioning
confidence: 92%
“…A topological study with BaMV showed that potexvirus TGB2 protein integrates into the ER membranes in a U-like structure with the central loop exposed to the ER lumen and with both the N- and C-terminus located on the cytoplasmic side of the ER (Hsu et al, 2008; Figure 1C ; TGB2). Cysteine-to-alanine substitution analysis indicated that two conserved cysteine residues (Cys 109 and Cys 112 ) in the C-terminal region of potexvirus TGB2 protein are critical for both cell-to-cell and systemic movement of BaMV (Hsu et al, 2008; Tseng et al, 2009). In addition, potexvirus TGB2 protein has sequence-independent RNA-binding activity (Cowan et al, 2002; Hsu et al, 2009).…”
Section: Three Tgb Proteins (Tgb1 Tgb2 and Tgb3)mentioning
confidence: 99%
“…This outcome was expected because NbRabG3f participates in BaMV replication, whereas NbRabGAP1 assists in the intercellular movement of BaMV. Similar to PVX, the BaMV movement proteins TGBp2 and TGBp3 are ER-targeting membrane proteins (Hsu et al, 2008). The BaMV infectious complex has been proposed to move from perinuclear ER-derived membrane-bound bodies (MBB) to the plasmodesmata (Wu et al, 2011; Liou et al, 2015).…”
Section: A Host Factor Possibly Involved In Bamv Vesicle Trafficking mentioning
confidence: 99%
“…Results from multiple studies have predicted that TGB2 proteins form a U-shaped membrane domain with the central connecting loop in the ER lumen (e.g. Zamyatnin et al, 2006; Hsu et al, 2008). Consistent with these findings are the results from Zamyatnin et al (2006), who used bimolecular fluorescence complementation (BiFC) to determine that the N- and C-termini of a hordei-like TGB2 protein were located in the cytoplasm.…”
Section: Intracellular Movement Of Plant Viruses With Mps Not Associamentioning
confidence: 99%